Conceitos e aspectos históricos da educação especial no Brasil - QUEIROZ, Fabiane da Silva Rodrigues (2023)
This work seeks to understand the trajectory of Special Education in Brazil, which is a teaching modality aimed at serving students with special needs in schools. For this, we will make a historical survey of the struggles that have taken place over the years through educational policies that have contributed to the inclusion of disabled people in the school environment.